Shielding around spallation neutron sources - Fragopoulou, M.; Manolopoulou, M.; Stoulos, S.; Brandt, R.; Westmeier, W.; Krivopustov, M.; Sosnin, A.; Golovatyuk, S.; Zamani, M. (HNPS Advances in Nuclear Physics, 2019)
Spallation neutron sources provide more intense and harder neutron spectrum than nuclear reactors for which a substantial amount of shielding measurements have been performed. Although the main part of the cost for a spallation station is the cost of the shielding, measurements regarding shielding for the high energy neutron region are still very scarce. In this work calculation of the neutron interaction length in polyethylene moderator for different neutron energies is presented. Measurements which were carried out in Nuclotron accelerator at the Laboratory of High Energies (Joint Institute for Nuclear Research, Dubna) and comparison with calculation are also presented. The measurements were performed with Solid State Nuclear Track Detectors (SSNTDs).